Positive pole piece and preparation method thereof, secondary battery and electric device
By adjusting the average particle size and specific surface area of lithium iron phosphate particles and reasonably matching nickel-cobalt lithium manganate particles, the serious gas production problem of hybrid systems in lithium-ion batteries is solved, and the safety and circulation performance of the battery are improved.
Patent Information
- Application Number
- CN202410026235.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-01-08
AI Technical Summary
Among the existing lithium-ion batteries, the mixed system of nickel-cobalt lithium manganate materials and lithium iron phosphate materials has serious gas production problems, which affects the safety and life of the battery.
By adjusting the average particle size and specific surface area of the lithium iron phosphate particles, it is controlled within the range of 500-3000 nm and 3-8 m2/g, its water absorption is reduced, and the nickel-cobalt lithium manganate particles are reasonably matched in the positive electrode active layer.
It significantly reduces the moisture content of the positive electrode active material, reduces the gas production level of the secondary battery, improves the safety and circulation performance of the battery, and takes into account the capacity of grams.
Smart Images

Figure CN119852311A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode sheet and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Nickel cobalt manganese oxide materials and lithium iron phosphate salt materials are commonly used lithium ion positive electrode active materials. In order to reduce the cost of lithium ion batteries, nickel cobalt manganese oxide materials and lithium iron phosphate salt materials can be used in combination, but this type of positive electrode active material produces serious gas, which will greatly affect the safety and life of the battery. How to improve the above problems of the mixed system of lithium iron phosphate materials and nickel cobalt manganese oxide ternary materials is of great significance. Summary of the invention
[0004] This application is made in view of the above-mentioned subject, and aims to solve at least one of the technical problems existing in the prior art. To this end, this application provides a positive electrode plate and a preparation method, a secondary battery and an electrical device. The positive electrode plate of this application reduces the degree of gas production while also taking into account the gram capacity of the secondary battery.
[0005] A first aspect of the present application provides a positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode active layer, the positive electrode active layer being arranged on at least one side of the current collector,
[0006] The positive electrode active layer includes at least a first positive electrode active layer formed on the current collector, and a second positive electrode active layer formed on a side of the first positive electrode active layer away from the current collector.
[0007] The first positive electrode active layer comprises lithium iron phosphate particles, and the second positive electrode active layer comprises lithium nickel cobalt manganese oxide particles; or,
[0008] The first positive electrode active layer includes lithium nickel cobalt manganese oxide particles, and the second positive electrode active layer includes lithium iron phosphate salt particles;
[0009] The primary average particle size of the lithium iron phosphate salt particles is 500-3000 nm, and the BET specific surface area of the lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.
[0010] The electrochemical properties of lithium iron phosphate particles are usually improved by nano-sizing the lithium iron phosphate particles. However, the specific surface area of the nano-sized lithium iron phosphate particles is too large, which leads to severe water absorption. During the cycle of the battery cell, the high water content of the electrode is likely to lead to an increase in interfacial side reactions, thereby increasing the degree of gas production, seriously endangering the safety performance and service life of the secondary battery. Due to the above-mentioned problems of lithium iron phosphate particles, the gas production problem of the positive electrode active material mixed with the upper and lower layers of lithium iron phosphate particles and nickel cobalt manganese oxide particles is also very prominent. The present application controls the primary average particle size of the lithium iron phosphate particles to 500-3000nm, and further adjusts its specific surface area to 3m 2 / g-8m 2 / g. A lower specific surface area has a lower specific surface energy, which is beneficial to reducing the water absorption of the material, thereby reducing the water content of the positive electrode active material during processing and storage. At the same time, a lower specific surface area is also beneficial to the volatilization of water in the material, which is beneficial to further reduce the water content of the positive electrode active material. However, excessively large particle size and too low specific surface area will affect its kinetic properties and reduce the gram capacity of the positive electrode active material. The positive electrode active material of the present application increases the primary average particle size of the lithium iron phosphate salt particles and reduces its specific surface area, controls the two within a reasonable range, greatly reduces the water content of the positive electrode active material, thereby reducing the gas production of the secondary battery, improving the safety performance and cycle performance of the secondary battery, while also taking into account the gram capacity of the positive electrode active material.
[0011] In any embodiment, the primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
[0012] Controlling the primary average particle size of the lithium iron phosphate salt particles within a suitable range is beneficial to further balance the gas generation degree and the gram capacity of the secondary battery.
[0013] In any embodiment, the specific surface area of the lithium iron phosphate particles is BET 4m 2 / g-7m 2 / g.
[0014] The BET of the lithium iron phosphate particles is controlled at 4m 2 / g-7m 2 / g, which is beneficial to further balance the gas production level and the gram capacity of the secondary battery.
[0015] In any embodiment, calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, and the ratio z of the specific surface area BET of the lithium iron phosphate salt particles to Cx satisfies 1.5≤z≤8.5. Optionally, the ratio z of the specific surface area BET of the lithium iron phosphate salt particles to Cx satisfies 3≤z≤6.
[0016] In the present application, the ratio z of the specific surface area BET of the lithium iron phosphate salt particles to the Cx can characterize the uniform density of the carbon contained in the lithium iron phosphate salt particles. When the primary average particle size and carbon content of the lithium iron phosphate salt particles remain unchanged, the lower the ratio z, the more uniform and dense the carbon contained in the lithium iron phosphate salt particles. Improving the uniform density of the contained carbon is conducive to improving the kinetic performance and gram capacity of the lithium iron phosphate salt particles, but too high carbon density will affect the insertion and extraction of lithium ions, thereby affecting the kinetic performance and gram capacity of the secondary battery. The z ratio range of the present application is conducive to the carbon contained in the lithium iron phosphate salt particles having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the gram capacity and kinetic performance of the secondary battery. Further, the discharge voltage range of the nickel cobalt manganese oxide particles is higher. In the double-layer positive electrode active material, improving the kinetic performance of the lithium iron phosphate salt particles is more conducive to its coordinated discharge with the nickel cobalt manganese oxide particles, which is conducive to further improving the overall kinetic performance of the positive electrode active material.
[0017] In any embodiment, the carbon content of the lithium iron phosphate salt particles is 0.8 wt% to 2.0 wt% based on the total weight of the lithium iron phosphate salt particles. Optionally, the carbon content of the lithium iron phosphate salt particles is 1.0 wt% to 1.6 wt% based on the total weight of the lithium iron phosphate salt particles.
[0018] The carbon content range of the present application helps to further increase the gram capacity of the secondary battery while reducing the impact on its water absorption degree.
[0019] In any embodiment, the lithium iron phosphate particles have a molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤z1≤4, 0<q1≤0.1, and / or
[0020] The lithium nickel cobalt manganese oxide particles have a molecular formula of LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, wherein R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
[0021] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb. Optionally, the Q is Ti.
[0022] Doping the above elements in lithium iron phosphate particles and / or nickel cobalt manganese oxide particles helps to improve the ion transport capacity of the positive electrode active material. Furthermore, the discharge performance requirements of nickel cobalt manganese oxide particles are relatively high. In the double-layer positive electrode active material, improving the kinetic properties of lithium iron phosphate particles is more conducive to its coordinated discharge with nickel cobalt manganese oxide particles, thereby helping to further improve the overall kinetic properties of the positive electrode active material.
[0023] In any embodiment, based on the total weight of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm. Optionally, based on the total weight of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 2500-6000 ppm.
[0024] The Q element content in existing lithium iron phosphate particles is generally low or no Q element is added. The range of Q element in the present application helps to balance the primary average particle size on the basis of further improving the kinetic performance and gram capacity of the positive electrode active material.
[0025] In any embodiment, the capacity ratio of the lithium iron phosphate salt particles is η≥88%, where η is defined as:
[0026] The battery having the lithium iron phosphate particles as the positive electrode active material is charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, and η=C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0027] The capacity ratio η of the lithium iron phosphate salt particles can reflect its dynamic performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the lithium iron phosphate salt particles. The η value of the lithium iron phosphate salt particles in the present application is ≥88%, which has good dynamic performance.
[0028] In any embodiment, the lithium iron phosphate salt particles satisfy at least one of (a)-(f):
[0029] a) the Dv10 of the lithium iron phosphate particles is ≥200nm;
[0030] b) the Dv50 of the lithium iron phosphate particles is 500-5000nm;
[0031] c) the Dv90 of the lithium iron phosphate particles is ≤10000nm;
[0032] d) the Dv99 of the lithium iron phosphate particles is ≤12000nm;
[0033] e) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ;
[0034] f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0035] By making the lithium iron phosphate salt particles satisfy at least one of (a)-(g), the lithium iron phosphate salt particles can better achieve the technical effect of the present application.
[0036] In any embodiment, when the first positive electrode active layer includes lithium iron phosphate particles and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles, the coating weight of the first positive electrode active layer is 0.02-0.38 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.08-0.32g / 1540mm 2 ;
[0037] When the first positive electrode active layer includes nickel cobalt manganese oxide particles, and the second positive electrode active layer includes lithium iron phosphate particles, the coating weight of the first active layer is 0.08-0.32 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.02-0.38g / 1540mm 2 ;
[0038] Optionally,
[0039] When the first positive electrode active layer includes lithium iron phosphate particles and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles, the coating weight of the first positive electrode active layer is 0.05-0.32 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.1-0.28g / 1540mm 2 ;
[0040] When the first positive electrode active layer includes nickel cobalt manganese oxide particles and the second positive electrode active layer includes lithium iron phosphate particles, the coating weight of the first active layer is 0.1-0.28 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.05-0.32g / 1540mm 2 .
[0041] Controlling the gram weight of the first or second positive electrode active layer containing lithium iron phosphate particles and the second or first positive electrode active layer containing nickel cobalt manganese oxide particles within the scope of the present application helps to reduce the cost of positive electrode active materials while still obtaining a good gram capacity.
[0042] In any embodiment, the total thickness of the positive electrode active layer is 50-150 μm. Optionally, the total thickness of the positive electrode active layer is 60-90 μm.
[0043] The thickness of the positive electrode active material of the present application helps to maintain good kinetic performance and volume energy density.
[0044] In any embodiment, the first positive electrode active layer includes lithium iron phosphate salt particles, and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles.
[0045] Placing lithium iron phosphate salt particles in the first active layer is more conducive to improving the electrical performance of the secondary battery.
[0046] In any embodiment, the lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0047] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:
[0048] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0049] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0050] Compared with the traditional method of using high temperature to achieve particle growth, the lithium iron phosphate salt particles of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing lithium iron phosphate salt particles with the primary average particle size and specific surface area of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application synthesizes large particles at low temperature, which is conducive to reducing floating carbon and improving the consistency and uniformity of the surface carbon coating.
[0051] In any embodiment, the lithium iron phosphate salt particles are mainly obtained by the following preparation method: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and sintering at least twice, wherein:
[0052] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0053] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0054] In the preparation method of the embodiment of the present application, adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product. Further, by controlling the temperature of the first sintering and the carbon content of the intermediate after the first sintering within the above range, it is helpful to increase the primary particle size of the lithium iron phosphate salt particle precursor obtained after the first sintering. Specifically, in the first sintering, a lower carbon content is conducive to reducing the barrier effect of the carbon layer on the growth process of the lithium iron phosphate particles, which is conducive to the crystal growth of the lithium iron phosphate salt particle precursor at a lower temperature. At the same time, it is also conducive to the solid-phase diffusion reaction between the modifier that may be added and the lithium iron phosphate salt material, thereby facilitating the realization of a higher concentration of metal ion doping. By controlling the temperature of the second sintering and the carbon content of the sintered material within the above range, it is helpful to better coat the carbon on the surface of the lithium iron phosphate salt particles, forming a uniform and dense carbon coating layer, which is conducive to improving the surface conductivity of the lithium iron phosphate particles, and improving its kinetic properties and gram capacity.
[0055] In any embodiment, the method for preparing the lithium iron phosphate salt particles comprises the following steps:
[0056] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:
[0057] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0058] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0059] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possible doping elements on the lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain lithium iron phosphate salt particles having the primary average particle size of the present application.
[0060] A second aspect of the present application provides a secondary battery, which includes the positive electrode plate as described in the present application.
[0061] A third aspect of the present application provides an electrical device, which includes the positive electrode plate as described in the present application or the secondary battery as described in the present application.
[0062] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a slice diagram of the positive electrode sheet of Example 3 of the present application. Figure 1 a is a cross-section of the positive electrode under 1k times magnification; Figure 1 b is a slice image of the positive electrode under 3k times magnification.
[0064] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0065] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0066] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0067] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0068] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0069] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0070] Figure 8 This is a scanning electron microscope image of lithium iron phosphate salt particles with primary particle diameters marked according to one embodiment of the present application.
[0071] Description of reference numerals:
[0072] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0073] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0074] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0075] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0076] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0077] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0078] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0079] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0080] Due to the high cost, lithium nickel cobalt manganese oxide particles can be mixed with lithium iron phosphate to prepare a mixed positive electrode active layer coated on the upper and lower layers. Lithium iron phosphate particles have the problem of poor kinetic performance. In order to improve the electrical properties of lithium iron phosphate particles, they are usually nano-sized. Smaller particle size and larger specific surface area are conducive to improving their ability to transmit electrons. However, the specific surface area of nano-sized lithium iron phosphate particles is too large, resulting in serious water absorption. During the cycle of the battery cell, excessive water content in the pole piece is likely to lead to an increase in interfacial side reactions, thereby increasing the degree of gas production. At the same time, the high specific surface area will accelerate the side reactions between the positive electrode active material layer and the electrolyte at high voltage, seriously endangering the safety performance of the secondary battery. Therefore, the mixed positive electrode active layer has a more serious gas production phenomenon. The present application increases the primary average particle size of the lithium iron phosphate particles, reduces its BET value, and controls the two within a reasonable range by optimizing the lithium iron phosphate process and formula, while reducing the water absorption of the mixed positive electrode active material and taking into account the gram capacity of the mixed positive electrode active material.
[0081] [Positive electrode]
[0082] Based on this, the present application provides a positive electrode plate, the positive electrode plate includes a current collector and a positive electrode active layer, the positive electrode active layer is arranged on at least one side of the current collector,
[0083] The positive electrode active layer includes at least a first positive electrode active layer formed on the current collector, and a second positive electrode active layer formed on a side of the first positive electrode active layer away from the current collector.
[0084] The first positive electrode active layer includes lithium iron phosphate particles, and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles; or,
[0085] The first positive electrode active layer includes lithium nickel cobalt manganese oxide particles, and the second positive electrode active layer includes lithium iron phosphate salt particles;
[0086] The primary average particle size of lithium iron phosphate salt particles is 500-3000nm, and the specific surface area of lithium iron phosphate salt particles is 3m 2 / g-8m 2 / g.
[0087] In this application, the term "primary average particle size" refers to the average of the primary particle sizes of all particles, wherein the primary particle size refers to the longest distance between two points on the edge in the cross-sectional view. Figure 8 As shown in the scanning electron microscope image of lithium iron phosphate particles, the line segment marked by the double arrow in the particle is the primary particle size defined in this application
[0088] In the present application, the term "specific surface area" or "BET" refers to the total area per unit mass of particles. In the present application, the BET of lithium iron phosphate particles is related to factors such as the primary average particle size of the lithium iron phosphate particles, the carbon content, the density of the carbon coating, and the looseness and porosity of the particles.
[0089] In some embodiments, the lithium iron phosphate salt particles are primary particles.
[0090] In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation.
[0091] In some embodiments, the lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles.
[0092] In this article, the term "single crystal" refers to a crystal with a complete structure grown from a single crystal nucleus. The single crystal of the present application is a whole under the field of view of a transmission electron microscope photograph, and there is no grain boundary in the single crystal.
[0093] In some embodiments, the single crystal of the present application may have tiny defects, for example, micro-pores inside, a small number of points and surfaces, or a small number of particles adhering to each other on the surface of a particle.
[0094] As used herein, the term "polycrystalline" refers to a crystal composed of small single crystal particles randomly oriented together, with grain boundaries existing within the polycrystalline.
[0095] In some embodiments, based on the total number of lithium iron phosphate particles, the number of single crystal particles accounts for greater than or equal to 90%. When the number of single crystal particles is controlled within the above range, the proportion of single crystal particles is higher than that of polycrystalline and secondary agglomerates, which is conducive to reducing BET.
[0096] The primary average particle size of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the electrode perpendicular to the large surface of the positive electrode plate to expose the cross section, and the cross section is photographed by scanning electron microscopy. The boundary between the first positive electrode active layer and the second positive electrode active layer of the cross section is clear. The particle size of the positive electrode active layer containing lithium iron phosphate salt particles is statistically analyzed by long diameter statistical method. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size and of the lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. Among them, since particles with a primary particle size of 0 < ≤ 80nm are prone to adhesion, there is a large error in the statistics, and it is difficult to clearly identify them separately. Therefore, in the primary particle size statistics process, particles with a primary particle size of 0 < ≤ 80nm are not within the statistical range.
[0097] In order to improve the electrical properties of lithium iron phosphate particles, they are usually nano-sized. Smaller particle size and larger specific surface area are beneficial to improve their ability to transmit electrons. However, the specific surface area of nano-sized lithium iron phosphate particles is too large, which leads to severe water absorption. During the cycle of the battery cell, excessive water content in the electrode can easily lead to an increase in interfacial side reactions, thereby increasing the degree of gas production, seriously endangering the safety performance of the secondary battery. Due to the above-mentioned problems of lithium iron phosphate particles, the gas production problem of the positive electrode active material mixed with the upper and lower layers of lithium iron phosphate particles and nickel cobalt manganese oxide particles is also very prominent. The present application controls the primary average particle size of the lithium iron phosphate particles to 500-3000nm, and further adjusts its specific surface area to 3m 2 / g-8m 2 / g. A lower specific surface area has a lower specific surface energy, which is beneficial to reducing the water absorption of the material, thereby reducing the water content of the positive electrode active material during processing and storage. At the same time, a lower specific surface area is also beneficial to increasing the volatility of water in the material, thereby helping to further reduce the water content of the positive electrode active material. However, excessively large particle size and too low specific surface area will affect its kinetic properties and reduce the gram capacity of the positive electrode active material. The positive electrode active material of the present application increases the primary average particle size of the lithium iron phosphate salt particles and reduces its specific surface area, controls the two within a reasonable range, greatly reduces the water content of the positive electrode active material, and at the same time reduces the active specific surface area of the reaction under high voltage, thereby reducing the gas production of the secondary battery, improving the safety performance and cycle performance of the secondary battery, while also taking into account the gram capacity of the positive electrode active material.
[0098] In some embodiments, the primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
[0099] In some embodiments, the primary average particle size of the lithium iron phosphate particles can be 500nm, 550nm, 600nm, 650nm, 700nm, 730nm, 750nm, 780nm, 800nm, 830nm, 850nm, 870nm, 900nm, 950nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 2000nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm, 3000nm, or a value in the range composed of any two of the above primary average particle sizes.
[0100] Controlling the primary average particle size of the lithium iron phosphate salt particles within a suitable range is beneficial to further balance the gas generation degree and the gram capacity of the secondary battery.
[0101] In some embodiments, the specific surface area of the lithium iron phosphate particles is 4 m 2 / g-7m 2 / g.
[0102] In some embodiments, the specific surface area of the lithium iron phosphate particles can be 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m2 / g, 7.5m 2 / g, 8m 2 / g, or a value within the range consisting of any two of the above specific surface areas BET.
[0103] The BET specific surface area of the particles can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 19587-2017. As an example, lithium iron phosphate particles are taken as samples and placed in a sample tube, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The sample monolayer adsorption amount is obtained based on the BET multilayer adsorption theory and its formula, thereby obtaining the specific surface area of the sample.
[0104] If the BET of lithium iron phosphate particles is too high, it will increase its water absorption, causing serious gas production in the secondary battery. If the BET of lithium iron phosphate particles is too low, it will reduce its gram capacity. Control the BET of lithium iron phosphate particles within 4m 2 / g-7m 2 / g, which is beneficial to further balance the gas production level and the gram capacity of the secondary battery.
[0105] In some embodiments, based on the total weight of the lithium iron phosphate particles, the carbon content of the lithium iron phosphate particles is Cx weight %, and the ratio z of the specific surface area BET of the lithium iron phosphate particles to Cx satisfies 1.5≤z≤8.5.
[0106] In some embodiments, the ratio z of the specific surface area BET of the lithium iron phosphate salt particles to Cx satisfies 3≤z≤6.
[0107] In some embodiments, the z can be 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.3, 4.5, 4.8, 5, 5.3, 5.5, 5.8, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, 7.8, 8, 8.3, 8.5, or a value in the range consisting of any two of the above z values.
[0108] In the present application, the ratio z of the specific surface area BET to Cx of the lithium iron phosphate salt particles can characterize the uniform density of the carbon contained in the lithium iron phosphate salt particles. When the primary average particle size and carbon content of the lithium iron phosphate salt particles remain unchanged, the lower the ratio z, the higher the carbon coating utilization rate in the particles, the less floating carbon, and the more uniform and dense the carbon contained in the lithium iron phosphate salt particles. Improving the uniform density of the contained carbon is conducive to improving the kinetic performance and gram capacity of the lithium iron phosphate salt particles. However, too high carbon density may affect the insertion and extraction of lithium ions, and to a certain extent affect the kinetic performance and gram capacity of the secondary battery. The z ratio range of the present application is conducive to the carbon contained in the lithium iron phosphate salt particles having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the gram capacity and kinetic performance of the secondary battery. Furthermore, the discharge performance requirements of nickel cobalt manganese oxide lithium particles are relatively high. In the double-layer positive electrode active material, improving the kinetic properties of lithium iron phosphate salt particles is more conducive to its coordinated discharge with lithium nickel cobalt manganese oxide particles, thereby helping to further improve the overall kinetic properties of the positive electrode active material.
[0109] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 0.8 wt % to 2.0 wt %, calculated based on the total weight of the lithium iron phosphate salt particles.
[0110] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 1.0 wt % to 1.6 wt %, calculated based on the total weight of the lithium iron phosphate salt particles.
[0111] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 0.8 weight %, 0.9 weight %, 1.0 weight %, 1.1 weight %, 1.2 weight %, 1.3 weight %, 1.4 weight %, 1.5 weight %, 1.6 weight %, 1.7 weight %, 1.8 weight %, 1.9 weight %, 2.0 weight %, or a value in the range of any two of the above carbon contents, calculated based on the total weight of the lithium iron phosphate salt particles.
[0112] The carbon content of the ferric phosphate particles can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 20123-2006 / ISO 15350:2000.
[0113] In some embodiments, the carbon contained in the lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.
[0114] Increasing the carbon content of lithium iron phosphate particles helps to increase the gram capacity of the secondary battery, but too high a carbon content may increase the degree of water absorption. The carbon content range of the present application helps to further increase the gram capacity of the secondary battery while reducing the impact on its water absorption degree.
[0115] In some embodiments, the lithium iron phosphate salt particles have the molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤z1≤4, 0<q1≤0.1, and / or
[0116] Lithium nickel cobalt manganese oxide particles have the molecular formula LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, wherein R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
[0117] In some embodiments, the lithium iron phosphate salt particles have the molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , m1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x1 can be 0.9, 1.0, y1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, z1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.
[0118] In some embodiments, Q comprises at least one of Ti, V, Mg, and Nb. In some embodiments, Q is Ti.
[0119] In some embodiments, the lithium nickel cobalt manganese oxide particles have the molecular formula LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2O2, x2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, y2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, z2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0<x2+y2+z2<1. In some embodiments, the ratio of lithium and oxygen content in the lithium nickel cobalt manganese oxide particles will fluctuate during battery formation and cycling.
[0120] Doping the above elements in lithium iron phosphate particles and / or nickel cobalt manganese oxide particles helps to improve the ion transport capacity of the positive electrode active material. The above elements can explain vacancies in the particle lattice or change the interatomic bond length, facilitating the movement of lithium ions in the lattice, thereby effectively improving the conductivity of the particles themselves, and improving the kinetic properties and gram capacity of the positive electrode active material. Furthermore, the discharge performance requirements of nickel cobalt manganese oxide particles are relatively high. In the double-layer positive electrode active material, improving the kinetic properties of lithium iron phosphate particles is more conducive to its coordinated discharge with nickel cobalt manganese oxide particles, which is conducive to further improving the overall kinetic properties of the positive electrode active material.
[0121] In some embodiments, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0122] In some embodiments, the content of Q in the lithium iron phosphate salt particles is 2500-6000 ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0123] In some embodiments, the Q content in the lithium iron phosphate salt particles is 1000ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, or a value in the range consisting of any two of the above Q contents.
[0124] The content of Q in the lithium iron phosphate salt particles, for example, the content of Ti, can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 33822-2017.
[0125] The Q element content in existing lithium iron phosphate salt particles is generally low or no Q element is added. Increasing the Q element content in lithium iron phosphate salt particles helps to further improve the bulk ion transport capacity of lithium iron phosphate salt particles. However, as the Q element content further increases, the bulk ion transport capacity may not continue to increase, and it may also affect the primary average particle size of the lithium iron phosphate salt particles. The range of the Q element in this application helps to balance its primary average particle size on the basis of further improving the kinetic performance and gram capacity of the positive electrode active material.
[0126] In some embodiments, the capacity of the lithium iron phosphate particles is η≥88%, where η is defined as:
[0127] The battery having the lithium iron phosphate particles as the positive electrode active material is charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, and η=C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0128] In some embodiments, the capacity proportion η of the lithium iron phosphate salt particles can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or a value in the range of any two of the above η values.
[0129] The η value of lithium iron phosphate salt particles can be measured by methods and equipment known in the art. As an example, firstly, a button cell is prepared with lithium iron phosphate salt particles as the positive electrode active material. The specific button cell preparation process is as follows: 2.0000g of lithium iron phosphate salt particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode sheet. Weigh the weight of the positive electrode sheet, wherein the loading amount of lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0130] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V was extracted and recorded as C1, and the capacity value at a discharge voltage of 2.0V was extracted and recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0131] The capacity ratio η of the lithium iron phosphate salt particles can reflect its kinetic performance and platform retention performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the lithium iron phosphate salt particles. The η value of the lithium iron phosphate salt particles in this application is ≥88%, which has good kinetic performance. At the same time, when the η value is high, the secondary battery can still maintain good power performance when discharged to a low SOC, that is, the battery with a high η value has a smaller voltage drop value when discharged at a low power and a large current.
[0132] In some embodiments, the lithium iron phosphate salt particles satisfy at least one of (a)-(f):
[0133] a) Dv10 of lithium iron phosphate particles ≥ 200nm;
[0134] b) Dv50 of lithium iron phosphate particles is 500-5000nm;
[0135] c) Dv90 of lithium iron phosphate particles ≤ 10000nm;
[0136] d) Dv99 of lithium iron phosphate particles ≤ 12000nm;
[0137] e) The powder compaction density of lithium iron phosphate at 3T pressure is ≥2.25g / cm 3 ;
[0138] f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0139] As used herein, the term "Dv10" refers to the particle size corresponding to the particle having a volume cumulative particle size distribution percentage of 10%.
[0140] As used herein, the term "Dv90" refers to the particle size at which the volume cumulative particle size distribution percentage in the particles reaches 90%.
[0141] As used herein, the term "Dv99" refers to the particle size corresponding to the 99% cumulative particle size distribution percentage in the particles.
[0142] In this article, the term "powder compaction density" refers to the density of a compact with a certain density and strength formed when the powder moves and deforms during the external compression process, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced. The unit is g / cm 3 .
[0143] In some embodiments, the lithium iron phosphate salt particles have a Dv10<Dv50.
[0144] In some embodiments, the lithium iron phosphate salt particles have a Dv90>Dv50.
[0145] In some embodiments, the Dv50 of the lithium iron phosphate particles can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a value in the range composed of the Dv50 of any two of the above second crushing products.
[0146] The Dv10, Dv50, Dv90 and Dv99 of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077.1-2016 using a laser particle size analyzer (Malvern Master Size 3000).
[0147] Under different pressures, the powder compaction density of lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 24533-2009 can be referred to and measured using a compaction density instrument. Specifically, a certain amount of lithium iron phosphate salt particles are placed on a special compaction mold (the mold diameter is known), and the mold is hollow in the middle and has a metal disc above and below. The lithium iron phosphate salt particles are placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on the compaction density instrument. Different pressures (for example, 3T) can be set. The thickness of the lithium iron phosphate salt particles under different pressures can be read on the device. The powder compaction density of the lithium iron phosphate salt particles is ρ=m / v, where v=(S×H), m is the mass of the lithium iron phosphate salt particles, S is the bottom area of the mold, and H is the thickness of the lithium iron phosphate salt particles after compaction.
[0148] The powder resistivity of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 33822-2017 can be referred to and a powder resistivity meter (Suzhou Jingge, ST2722 model) can be used for measurement. Specifically, a certain amount of lithium iron phosphate salt particles (for example, 1g) is weighed and added to the feeding chamber of the powder resistivity meter, and a pressure of 8MPa is applied. The forward resistivity and reverse resistivity of the lithium iron phosphate salt particles are tested respectively, and the average value of the two is taken as the powder resistivity of the lithium iron phosphate salt particles.
[0149] By making the lithium iron phosphate salt particles satisfy at least one of (a)-(g), the lithium iron phosphate salt particles can better achieve the technical effect of the present application.
[0150] In some embodiments, when the first positive electrode active layer includes lithium iron phosphate particles and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles, the coating weight of the first positive electrode active layer is 0.02-0.38 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.08-0.32g / 1540mm 22 ;
[0151] When the first positive electrode active layer includes nickel cobalt manganese oxide particles and the second positive electrode active layer includes lithium iron phosphate particles, the coating weight of the first active layer is 0.08-0.32 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.02-0.38g / 1540mm 2 .
[0152] In some embodiments, when the first positive electrode active layer includes lithium iron phosphate particles and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles, the coating weight of the first positive electrode active layer is 0.05-0.32 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.1-0.28g / 1540mm 2 ;
[0153] When the first positive electrode active layer includes nickel cobalt manganese oxide particles and the second positive electrode active layer includes lithium iron phosphate particles, the coating weight of the first active layer is 0.1-0.28 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.05-0.32g / 1540mm 22 .
[0154] In some embodiments, the coating weight of the first or second layer of positive electrode active material including lithium iron phosphate particles may be 0.02 g / 1540 mm 2 , 0.04g / 1540mm 2 , 0.06g / 1540mm2 , 0.08g / 1540mm 2 , 0.10g / 1540mm 2 , 0.12g / 1540mm 2 , 0.14g / 1540mm 2 , 0.15g / 1540mm 2 , 0.16g / 1540mm 2 , 0.18g / 1540mm 2 , 0.20g / 1540mm 2 , 0.22g / 1540mm 2 , 0.24g / 1540mm 2 , 0.26g / 1540mm 2 , 0.28g / 1540mm 2 , 0.30g / 1540mm 2 , 0.32g / 1540mm 2 , 0.34g / 1540mm 2 , 0.36g / 1540mm 2 , 0.38g / 1540mm 2 , or a value in the range consisting of any two of the above coating weights; the coating weight of the second / or first positive electrode active material comprising nickel cobalt manganese oxide particles can be 0.08g / 1540mm 2 , 0.10g / 1540mm 2 , 0.12g / 1540mm 2 , 0.14g / 1540mm 2 , 0.16g / 1540mm 2 , 0.18g / 1540mm 2 , 0.20g / 1540mm 2 , 0.22g / 1540mm 2 , 0.24g / 1540mm 2 , 0.25g / 1540mm 2 , 0.26g / 1540mm 2 , 0.28g / 1540mm 2 , 0.30g / 1540mm 2 , 0.32g / 1540mm 2 , or a value in a range consisting of any two of the above coating weights.
[0155] The coating weight of the first positive electrode active layer and the second positive electrode active layer can be measured by methods and equipment known in the art. As an example, a 1540 mm thick sheet is punched out of the positive electrode sheet. 2The first positive electrode active layer and the second positive electrode active layer are separated, and the second positive electrode active layer and the second positive electrode active layer are weighed.
[0156] Controlling the gram weight of the first or second positive electrode active layer containing lithium iron phosphate particles and the second or first positive electrode active layer containing nickel cobalt manganese oxide particles within the scope of the present application helps to reduce the cost of positive electrode active materials while still obtaining a good gram capacity.
[0157] In some embodiments, the total thickness of the positive electrode active layer is 50-150 μm.
[0158] In some embodiments, the total thickness of the positive electrode active layer is 60-90 μm.
[0159] In some embodiments, the total thickness of the positive electrode active layer can be 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or a value in the range consisting of the total thickness of any two of the above positive electrode active layers.
[0160] The thickness of the positive electrode active layer can be measured using a micrometer.
[0161] The thickness of the positive electrode active material of the present application helps to maintain good kinetic performance and volume energy density.
[0162] In some embodiments, the first positive electrode active layer includes lithium iron phosphate salt particles, and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles.
[0163] The compaction density of lithium iron phosphate particles is lower than that of lithium nickel cobalt manganese oxide particles. When they are located in the second positive electrode active layer away from the current collector, the gap will be reduced during the cold pressing of the pole piece, thereby affecting the infiltration of the electrolyte, causing the positive electrode polarization to increase, and to a certain extent affecting the performance of the battery cell. At the same time, lithium iron phosphate particles can also serve as a conductive transition layer between the current collector and lithium nickel cobalt manganese oxide particles, which is beneficial to improving the conductivity of the electrode. Therefore, placing lithium iron phosphate particles in the first active layer is more conducive to improving the electrical performance of the secondary battery.
[0164] In some embodiments, the lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0165] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:
[0166] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0167] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0168] In some embodiments, the temperature of the first sintering may be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, or a value in the range consisting of any two of the above first sintering temperatures; the temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, or a value in the range consisting of any two of the above second sintering temperatures.
[0169] In some embodiments, the heating rates of the first sintering and the second sintering are independently 2° C. / min-20° C. / min.
[0170] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.
[0171] In some embodiments, the constant temperature sintering time of the first sintering is 1-6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0172] In some embodiments, the constant temperature sintering time of the second sintering is 2-12 hours. In some embodiments, the constant temperature sintering time of the second sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours.
[0173] Compared to the traditional method of using high temperature to achieve particle growth, the lithium iron phosphate salt particles of the embodiment of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing lithium iron phosphate salt particles having the primary average particle size and specific surface area of the present application. Furthermore, controlling the heating rate, sintering temperature and constant temperature sintering time of the first sintering and / or the second sintering helps to reduce side reactions, thereby better preparing the lithium iron phosphate salt particles of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application performs large particle synthesis at low temperature, which is conducive to improving the consistency and uniformity of the surface carbon coating.
[0174] In some embodiments, the lithium iron phosphate salt particles are mainly obtained by the following preparation method: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings, wherein:
[0175] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0176] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0177] In some embodiments, the carbon content of the material after the first sintering can be 0.01 weight%, 0.05 weight%, 0.1 weight%, 0.15 weight%, 0.20 weight%, 0.25 weight%, 0.30 weight%, 0.35 weight%, 0.40 weight%, 0.45 weight%, 0.50 weight%, 0.55 weight%, 0.60 weight%, 0.65 weight%, 0.70 weight%, 0.75 weight%, 0.79 weight, or a value in the range consisting of any two of the above carbon contents; the carbon content of the material after the second sintering can be 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight%, or a value in the range consisting of any two of the above carbon contents.
[0178] In the preparation method of the embodiment of the present application, adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product. Further, by controlling the temperature of the first sintering and the carbon content of the intermediate after the first sintering within the above range, it is helpful to increase the primary particle size of the lithium iron phosphate salt particle precursor obtained after the first sintering. Specifically, during the first sintering process, the lower carbon content is conducive to reducing the barrier effect of the carbon layer on the growth process of the lithium iron phosphate particles, which is conducive to the crystal growth of the lithium iron phosphate salt particle precursor at a lower temperature. At the same time, it is also conducive to the solid-phase diffusion reaction between the modifier that may be added and the lithium iron phosphate salt material, thereby facilitating the realization of a higher concentration of metal ion doping. By controlling the temperature of the second sintering and the carbon content of the sintered material within the above range, it is helpful to better coat the carbon on the surface of the lithium iron phosphate salt particles to form a uniform and dense carbon coating layer, which is conducive to improving the surface conductivity of the lithium iron phosphate particles, and improving its kinetic properties and gram capacity.
[0179] In some embodiments, a raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent is provided, and sintering is performed at least twice.
[0180] In some embodiments, the mixing ratio of the lithium source, the iron source, and the phosphorus source satisfies, based on the atomic mole number of each element, Fe:P=(0.96-0.985):1, Li:Fe=(1.0-0.95):1.1.
[0181] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.
[0182] In some embodiments, the mixing ratio of the lithium source and the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.
[0183] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent is (9-0.25): 1. In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 0.8:1, 0.5:1 or 0.25:1.
[0184] In some embodiments, the lithium source is a lithium-containing compound. In some embodiments, the lithium source includes at least one of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide, and lithium acetate. In some embodiments, the lithium source includes lithium carbonate.
[0185] In some embodiments, the iron source is an iron-containing compound. In some embodiments, the iron source includes at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric oxyhydroxide. In some embodiments, the iron source includes ferric oxide.
[0186] In some embodiments, the phosphorus source is a phosphoric acid compound. In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. In some embodiments, the phosphorus source includes phosphoric acid.
[0187] In some embodiments, the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose, and lactose. In some embodiments, the carbon source comprises glucose.
[0188] In some embodiments, the carbon film-forming agent includes at least one of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol. In some embodiments, the carbon film-forming agent includes polyaniline.
[0189] In some embodiments, the modifier includes at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethoxide, niobium oxalate, niobium pentoxide, magnesium hydroxide, and magnesium nitrate. In some embodiments, the modifier includes titanium dioxide.
[0190] By using the raw materials in the above ratio, it is beneficial to form the lithium iron phosphate salt particles of the present application.
[0191] In some embodiments, the method for preparing lithium iron phosphate particles comprises the following steps:
[0192] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:
[0193] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0194] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0195] In the present application, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%.
[0196] In some embodiments, the Dv50 of the product after the first crushing can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, or a value in the range composed of the Dv50 of any two of the above products after the first crushing.
[0197] In some embodiments, the Dv50 of the product after the second crushing can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a value in the range composed of the Dv50 of any two of the above products after the second crushing.
[0198] In some embodiments, the pulverization includes one or more of mechanical crushing, grinding, sand milling, and air flow crushing.
[0199] The Dv50 of the particles can be measured using methods and equipment commonly used in the art. As an example, it can be measured using a laser particle size analyzer (Malvern Master Size 3000) with reference to GB / T19077.1-2016.
[0200] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possible doping elements on the lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain lithium iron phosphate salt particles having the primary average particle size of the present application.
[0201] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer includes a positive electrode active material, a binder and a conductive agent, and the positive electrode active material is the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.
[0202] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0203] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0204] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0205] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0206] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0207] [Negative electrode]
[0208] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0209] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0210] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0211] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0212] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0213] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0214] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0215] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0216] [Electrolytes]
[0217] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0218] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0219] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0220] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0221] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0222] [Isolation film]
[0223] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0224] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0225] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0226] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0227] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0228] [Secondary battery]
[0229] The present application provides a secondary battery, which includes the positive electrode sheet of the embodiment of the present application.
[0230] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0231] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0232] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0233] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0234] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0235] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0236] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0237] [Electrical devices]
[0238] In addition, the present application also provides an electrical device, which includes the positive electrode plate of the embodiment of the present application or the secondary battery of the embodiment of the present application.
[0239] In some embodiments, the power-consuming device of the embodiment of the present application may also include at least one of a battery module or a battery pack. The secondary battery, battery module, or battery pack may be used as a power source for the power-consuming device, or may be used as an energy storage unit for the power-consuming device. The power-consuming device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0240] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0241] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0242] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0243] Example
[0244] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0245] Example 1
[0246] 1. Preparation method
[0247] 1) Preparation of the first positive electrode active layer slurry
[0248] Preparation of lithium iron phosphate particles:
[0249] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratio of Li element, Fe element and P element is such that Fe:P=0.968:1; Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose and polyaniline added is such that after the first sintering, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.
[0250] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38%, a Dv50 of 400num, and spray dry (the negative pressure of the high-speed spray dryer is -650 to -200 Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for the first sintering, the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.
[0251] The obtained powder, glucose, polyaniline and water are mixed (based on the total weight of the lithium iron phosphate particles, the amount of glucose and polyaniline added meets the carbon content of the product after the second sintering is 1.2%, and the weight ratio of glucose and polyaniline meets glucose: polyaniline = 1:2), and the solid content of the mixture is 40%. After uniform mixing, the slurry is processed by ball milling and sand milling, and the Dv50 of the insoluble matter in the slurry is 550nm. The slurry is spray dried (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into the sintering furnace for the second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.
[0252] Lithium iron phosphate salt particles, conductive agent carbon black, binder polyvinylidene fluoride and dispersant polyvinyl pyrrolidone are mixed in a mass ratio of 93.0:4.0:2.5:0.5. The above materials containing positive electrode active materials are mixed and added into N-methylpyrrolidone for mixing and stirring. After being evenly dispersed, a first positive electrode slurry is prepared.
[0253] 2) Preparation of the second positive electrode active layer slurry
[0254] Lithium nickel cobalt manganese oxide particles (CPE-16, purchased from Guangdong Bangpu Recycling Technology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride are mixed in a mass ratio of 96.14:2.7:1.16. The above materials containing positive electrode active materials are mixed and added into N-methylpyrrolidone for mixing and stirring. After being evenly dispersed, a second positive electrode slurry is prepared.
[0255] 3) Preparation of positive electrode
[0256] The first positive electrode active layer slurry was prepared at 0.15 g / 1540 mm 2 The single-sided weight is evenly coated on the surface of the current collector aluminum foil, and the coating thickness is 39.75μm. The second positive electrode active layer slurry is 0.25g / 1540mm 2 The single-sided weight of the first positive electrode active slurry is evenly coated on the surface of the first positive electrode active slurry with a coating thickness of 47.2 μm, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet.
[0257] 4) Preparation of negative electrode sheet
[0258] Adding artificial graphite as a negative electrode active material, carbon black as a conductive agent, sodium carboxymethyl cellulose as a thickener, and styrene-butadiene rubber as a binder into deionized water in a mass ratio of 97.35:0.7:1:0.95, and stirring evenly to obtain a negative electrode slurry;
[0259] Then according to 216mg / 1540mm 2 The negative electrode slurry is coated on the copper foil with a double-sided weight, and the negative electrode sheet is obtained through drying, cold pressing and slitting;
[0260] 5) Preparation of isolation membrane
[0261] Polypropylene film is used as the isolation film.
[0262] 6) Preparation of batteries
[0263] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, the bare battery cell is welded with a pole ear, and the bare battery cell is placed in an aluminum shell and baked in a vacuum oven at 100°C for 8 hours, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static standing, hot and cold pressing, formation, shaping, capacity testing, etc. in sequence to obtain the lithium-ion battery of Example 1.
[0264] The preparation method of the battery of Examples 2-6 is similar to that of Example 1, but the primary average particle size and / or specific surface area of the lithium iron phosphate salt particles are adjusted. The specific material parameters are shown in Table 1. In the process of preparing the lithium iron phosphate salt particles, the difference from Example 1 is:
[0265] Example 2: Lowering the Dv50 of the mixed slurry after the first grinding to 450 nm;
[0266] Example 3: Increase the Dv50 of the mixed slurry after the first grinding to 900nm. Figure 1 a and 1b are respectively cross-sectional views of the positive electrode sheet of Example 3 under 1K and 3K magnification conditions;
[0267] Example 4: Increasing the Dv50 of the mixed slurry after the first grinding to 1100 nm;
[0268] Example 5: Reducing the Dv50 of the mixed slurry after the first grinding to 350nm;
[0269] Example 6: Increasing the Dv50 of the mixed slurry after the first grinding to 1200 nm.
[0270] The preparation methods of the batteries of Examples 7-9 are similar to those of Example 1, but the specific surface area and carbon content of the lithium iron phosphate particles are adjusted. The specific material parameters are shown in Table 1. In the process of preparing the lithium iron phosphate particles, the difference from Example 1 is that:
[0271] Example 7: The carbon content of the product after the second sintering is adjusted to 0.8%;
[0272] Example 8: The carbon content of the product after the second sintering is adjusted to 1.4%;
[0273] Example 9: The carbon content of the product after the second sintering is adjusted to 1.5%.
[0274] The preparation method of the battery of Example 10-11 is similar to that of Example 1, but the specific surface area value of the lithium iron phosphate salt particles is adjusted, and the specific material parameters are shown in Table 1. In the process of preparing the lithium iron phosphate salt particles, the difference from Example 1 is that;
[0275] Example 10: During the first sintering process, the weight ratio of glucose to polyaniline is 1:4;
[0276] Example 11: During the first sintering process, the weight ratio of glucose to polyaniline was 1:0.5.
[0277] The preparation methods of the batteries of Examples 12-14 are similar to those of Example 1, but the content of the Q element is adjusted. The specific material parameters are shown in Table 1. In the process of preparing lithium iron phosphate particles, the difference from Example 1 is that:
[0278] Example 12: The temperature of the first sintering is controlled to be 590° C., the temperature of the second sintering is controlled to be 720° C., and the Ti content is 0 ppm;
[0279] Example 13: The temperature of the first sintering is controlled to be 620°C, the temperature of the second sintering is controlled to be 740°C, and the Ti content is controlled to be 2500ppm;
[0280] Example 14: The temperature of the first sintering was controlled to be 655°C, the temperature of the second sintering was controlled to be 755°C, and the Ti content was controlled to be 6000ppm.
[0281] The preparation methods of the batteries of Examples 15-17 are similar to those of Example 1, but the coating weight of the first positive electrode active layer is adjusted, as shown in Table 1.
[0282] The preparation method of Example 18 is similar to that of Example 1, but lithium nickel cobalt manganese oxide particles are used as the first positive electrode active layer, and lithium iron phosphate particles are used as the second positive electrode active layer.
[0283] The preparation method of the battery of Comparative Example 1 is similar to that of Example 1, but the lithium iron phosphate salt particles used are different from those of Example 1. The specific parameters of the lithium iron phosphate salt particles used in Comparative Example 1 are shown in Table 1. The preparation method of the lithium iron phosphate salt particles of Comparative Example 1 is as follows:
[0284] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratio of Li element, Fe element and P element is such that Fe:P=0.968:1; Li:Fe=1:0.98, the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2, and the amount of glucose added is such that after the first sintering, the carbon content accounts for 1.2% of the weight of the lithium iron phosphate particles. Add water to the above substances to obtain a mixture slurry.
[0285] Use a ball mill to mix the slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 400nm, and spray dry it (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace and sintered once. The heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 810℃, and the insulation time is 4h. After the material is cooled, the material is processed by air flow crushing or mechanical crushing to obtain lithium iron phosphate particles, and the Dv50 of the lithium iron phosphate particles is 300nm.
[0286] The preparation method of the battery of Comparative Example 2 is similar to that of Example 1, but the primary average particle size of the lithium iron phosphate salt particles is larger than that of Example 1, as shown in Table 1. In the process of preparing the lithium iron phosphate salt particles, the difference from Example 1 is that;
[0287] Comparative Example 2: The Dv50 of the product after the first pulverization is 1300nm, and the temperature of the second sintering is 780℃.
[0288] The preparation method of the battery of Comparative Example 3-4 is similar to that of Example 1, but the specific surface area and carbon content of the lithium iron phosphate salt particles are adjusted, as shown in Table 1. In the process of preparing the lithium iron phosphate salt particles, the difference from Example 1 is:
[0289] Comparative Example 3: The carbon content of the product after the second sintering is controlled to be 0.7%;
[0290] Comparative Example 4: The temperature of the second sintering is 770° C., and the carbon content of the product after the second sintering is controlled to be 2.1%.
[0291] 2. Battery performance test
[0292] 1. Performance test of positive electrode active materials
[0293] 1) Primary average particle size test method of lithium iron phosphate particles
[0294] An argon ion beam is used to cut the positive electrode plate perpendicularly to the large surface of the positive electrode plate to expose the cross section, which is photographed using a scanning electron microscope. The boundary between the first positive electrode active layer and the second positive electrode active layer of the cross section is clear. The particle size of the positive electrode active layer containing lithium iron phosphate particles is statistically analyzed using the long diameter statistical method. Specifically, the total number of lithium iron phosphate particles with a primary particle size greater than 80 nm and the primary particle size of the lithium iron phosphate particles with a primary particle size greater than 80 nm can be counted in the electron microscope scanning photograph. The primary average particle size of the lithium iron phosphate particles = the primary particle size of the total lithium iron phosphate particles / the total number of lithium iron phosphate particles.
[0295] Among them, since particles with a primary particle size of 0 < ≤ 80 nm are prone to adhesion, there are large errors in the statistics and it is difficult to clearly identify them individually. Therefore, in the primary particle size statistics process, particles with a primary particle size of 0 < ≤ 80 nm are not included in the statistical range.
[0296] 2) Test method for specific surface area of lithium iron phosphate particles
[0297] According to the GB / T19587-2017 test standard method, the gas adsorption method was used to test the specific surface area of lithium iron phosphate particles and nickel cobalt manganese acid particles. Specifically, lithium iron phosphate particles were taken as samples and placed in a sample tube. The sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby obtaining the specific surface area of the sample.
[0298] 3) Test method for carbon content of lithium iron phosphate particles
[0299] The carbon content of lithium iron phosphate particles was tested by infrared absorption method after burning them in a high-frequency induction furnace. The specific testing process was based on the standard GB / T 20123-2006 / ISO 15350:2000.
[0300] 4) Test method for the content of Q element (such as Ti element) in lithium iron phosphate particles
[0301] The test method for the Q element content of lithium iron phosphate particles is carried out in accordance with GB / T 33822-2017.
[0302] 5) Measurement of η value of lithium iron phosphate particles
[0303] First, a button cell is prepared using lithium iron phosphate particles as the positive electrode active material. The specific button cell preparation process is as follows: 2.0000g of lithium iron phosphate particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode. Weigh the weight of the positive electrode, where the loading amount of lithium iron phosphate particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0304] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V was extracted and recorded as C1, and the capacity value at a discharge voltage of 2.0V was extracted and recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0305] 2. Battery performance test
[0306] 1) Battery capacity test method
[0307] Place the battery in a 25℃ oven for 2 hours until the battery temperature remains at 25℃; discharge the battery at a constant current of 1 / 3C to 2.0V; pause for 5 minutes; charge the battery at a constant current of 1 / 3C to 4.35V, then charge at a constant voltage of 4.35V until the cutoff current is 0.05C; pause for 5 minutes;
[0308] Discharge the battery at 1 / 3C constant current to 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity of the battery can be calculated. Gram capacity = capacity / mass of positive electrode active material.
[0309] 2) Gas production test method
[0310] Take an appropriate amount of diethyl carbonate (DEC) to wipe the battery cell injection port, weld one end of a clean, oil-free hollow long joint to the battery cell injection port, and connect the other end of the long joint to a Teflon hose filled with silicone oil through a clamp. The other end of the hose is connected to a TDK plug-in pressure gauge filled with silicone oil through a joint coated with AB glue. Apply epoxy resin glue to the long joint, clamp and interface, and let it stand for 24 hours to fix and prevent air leakage.
[0311] Before testing, connect the pressure gauge to the power supply and adjust it to zero; fix the battery cell with a fixture and put it into the furnace for testing. The specific test steps are as follows:
[0312] (1) Stand at 45℃ for 2h; (2) Discharge the battery at 1C constant current to 2.0V; (3) Stand for 5min; (4) Charge at 1.2C constant current to 0.5Cn Ah; (5) Charge at 0.87C constant current to 0.3Cn Ah; (6) Charge at 1 / 3C constant current to 4.35V, then charge at 4.2V constant voltage with a cut-off current of 0.05C; (7) Stand for 5min; (8) Discharge at 1C constant current to 2.0V; (9) Stand for 5min; (10) Repeat steps (4) to (9) for 1000 times. If the gas production value reaches 0.35Mpa, stop the test.
[0313] The specific steps for testing Cn are: let the battery stand at 25℃ for 30 minutes; discharge at 1C constant current to 2.0V; let it stand for 5 minutes; charge at 1 / 3C constant current to 4.35V, then charge at 4.2V constant voltage with a cut-off current of 0.05C; let it stand for 5 minutes; discharge at 1C constant current to 2.0V (this step extracts the capacity Cn); let it stand for 5 minutes.
[0314] III. Analysis of test results of various embodiments and comparative examples
[0315] The batteries of the embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The parameters of the positive electrode active materials are shown in Table 1, and the performance test results are shown in Table 2.
[0316]
[0317] Table 2 Performance test results
[0318]
[0319] According to the results in the above table, it can be seen from Examples 1-18 and Comparative Example 1 that increasing the primary average particle size of the lithium iron phosphate salt particles and reducing their specific surface area can reduce the gas production of the positive electrode plate coated with a double-layer positive electrode active material of lithium iron phosphate salt particles and nickel cobalt lithium manganese oxide particles. It can be seen from Examples 1-18 and Comparative Example 2 that when the primary average particle size of the lithium iron phosphate salt particles is too large, the gram capacity and kinetic performance of the secondary battery will be reduced. It can be seen from Examples 1-18 and Comparative Examples 3-4 that when the BET of the lithium iron phosphate salt particles is too small, the gram capacity of the secondary battery will be reduced, and when the BET of the lithium iron phosphate particles is too large, the gas production of the secondary battery will increase. In summary, when the primary average particle size of the lithium iron phosphate salt particles is 500-3000nm and the specific surface area BET is 3m 2 / g-8m 2 / g, the gas generation level of the secondary battery can be reduced while taking into account the gram capacity of the secondary battery.
[0320] It can be seen from Examples 1-6 that when the primary average particle size of the lithium iron phosphate particles is controlled to be 500-3000 nm, the gas generation level of the secondary battery can be reduced while taking into account the gram capacity of the secondary battery.
[0321] From Example 1 and Examples 7-9, it can be seen that the BET value of the lithium iron phosphate particles is controlled to be 3m 2 / g-8m 2 / g, the gas generation level of the secondary battery can be reduced while taking into account the gram capacity of the secondary battery.
[0322] It can be seen from Example 1 and Examples 10-11 that increasing the proportion of the carbon source film-forming agent is beneficial to achieving dense coating of the carbon layer. The dense degree of carbon coating in the present application is beneficial to further improving the kinetic performance and gram capacity of the secondary battery.
[0323] It can be seen from Example 1 and Examples 12-14 that adding metal elements, such as titanium, to lithium iron phosphate salt particles can improve the kinetic properties of the positive electrode active material. Further, increasing the content of the metal element, for example, within the range of 1000-10000 ppm, is conducive to further improving the kinetic properties and minimally affecting the primary average particle size of the lithium iron phosphate salt particles.
[0324] It can be seen from Examples 1 and 15-17 that reducing the content of the positive electrode active layer containing lithium iron phosphate particles in the double-layer positive electrode active layer can increase the gram capacity of the secondary battery, but it will increase the cost of the secondary battery. The gram weight of the positive electrode active layer containing lithium iron phosphate particles is controlled at 20-150 g / m 2 Within this range, it is beneficial to control the cost of the secondary battery while further improving the gram capacity of the secondary battery.
[0325] It can be seen from Example 1 and Example 18 that placing the lithium iron phosphate salt particles in the first positive electrode active layer close to the current collector is beneficial to further improve the gram capacity of the secondary battery.
[0326] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the current collector. The positive electrode active layer includes at least a first positive electrode active layer formed on the current collector, and a second positive electrode active layer formed on a side of the first positive electrode active layer away from the current collector. The first positive electrode active layer comprises lithium iron phosphate particles, and the second positive electrode active layer comprises lithium nickel cobalt manganese oxide particles; or, The first positive electrode active layer includes lithium nickel cobalt manganese oxide particles, and the second positive electrode active layer includes lithium iron phosphate salt particles; The primary average particle size of the lithium iron phosphate salt particles is 500-3000 nm, and the BET specific surface area of the lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.
2. The positive electrode sheet according to claim 1, characterized in that: The primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The specific surface area of the lithium iron phosphate particles is 4 m 2 / g-7m 2 / g.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 0.8 wt % to 2.0 wt %.
5. The positive electrode sheet according to claim 4, characterized in that: Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 1.0 wt % to 1.6 wt %.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The lithium iron phosphate particles have a molecular formula of Li m1 Fe x1 P y1 O z1 Q q1 , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤z1≤4, 0<q1≤0.1, and / or The lithium nickel cobalt manganese oxide particles have a molecular formula of LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, wherein R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
7. The positive electrode sheet according to claim 6, characterized in that: The Q includes at least one of Ti, V, Mg, and Nb.
8. The positive electrode sheet according to claim 6 or 7, characterized in that: Calculated based on the total weight of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The capacity proportion of the lithium iron phosphate salt particles is η≥88%, and η is defined as: The battery with the lithium iron phosphate particles as the positive electrode active material is charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted to discharge to 2.0V is recorded as C2, and η=C1 / C2. The charging process includes constant voltage charging, constant voltage 3.75V, and constant voltage cut-off current 50uA.
10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The lithium iron phosphate salt particles satisfy at least one of (a) to (f): a) the Dv10 of the lithium iron phosphate particles is ≥200nm; b) the Dv50 of the lithium iron phosphate particles is 500-5000nm; c) the Dv90 of the lithium iron phosphate particles is ≤10000nm; d) the Dv99 of the lithium iron phosphate particles is ≤12000nm; e) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ; f) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: When the first positive electrode active layer includes lithium iron phosphate particles and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles, the coating weight of the first positive electrode active layer is 0.02-0.38 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.08-0.32g / 1540mm 2 ; When the first positive electrode active layer includes nickel cobalt manganese oxide particles and the second positive electrode active layer includes lithium iron phosphate particles, the coating weight of the first positive electrode active layer is 0.08-0.32 g / 1540 mm 2 The coating weight of the second positive electrode active layer is 0.02-0.38g / 1540mm 2 .
12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: The total thickness of the positive electrode active layer is 50-150 μm.
13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The first positive electrode active layer includes lithium iron phosphate salt particles, and the second positive electrode active layer includes lithium nickel cobalt manganese oxide particles.
14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, and a phosphorus source, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500℃-760℃; The temperature of the second sintering is 700℃-800℃.
15. The positive electrode sheet according to claim 14, characterized in that: The lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%; The carbon content of the material after the second sintering is 0.8 wt%-2.0 wt%.
16. The positive electrode sheet according to claim 14 or 15, characterized in that: The preparation method of the lithium iron phosphate salt particles comprises the following steps: The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm.
17. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to any one of claims 1 to 16.
18. An electrical device, characterized in that: The electrical device comprises the positive electrode sheet according to any one of claims 1 to 16 or the secondary battery according to claim 17.
Citation Information
Patent Citations
Lithium battery anode material, lithium battery anode and preparing method thereof, and lithium battery
CN107732237A
Positive electrode active material, positive electrode plate, battery cell, battery, battery pack and electric equipment
CN115763725A
Positive pole piece, lithium ion secondary battery, battery module, battery pack and electric device
CN115842114A
Electrode and lithium-ion battery
US20190267664A1
Positive Electrode for Lithium Secondary Battery with Primer Layer Comprising Lithium Iron Phosphate
US20230170480A1
Cited By
Positive pole piece, preparation method thereof and lithium ion battery
CN120432495A
Composite positive pole piece, preparation method and application thereof and lithium ion battery
CN121885534A
Positive pole piece, preparation method, secondary battery and electrical apparatus
WO2025148418A1